Praksa na Fakulteti za socialno delo v času izrednih razmer - Kodele, Tadeja (Socialno delo, 2021)
Practical training is an important part of social work education. During the covid-19 pandemic, measures to contain the spread of the virus required a number of adjustments (cooperation with users remotely, reducing practice hours etc.) that created new challenges for students and mentors. In the article, the experience of conducting practical training for social work in Slovenia during the first wave of the covid-19 epidemic is presented from the perspective of mentors and students. The results of the research show that the stakeholders have different levels of satisfaction with the implementation of the practice in changed circumstances. Students’ challenges were mainly related to the inability to collaborate with users, and the additional burden of adapting the study process, and mentors’ challenges were related to how to provide quality mentoring and facilitate the expected experience under such circumstances. Due to the changed situation, students acquired several new skills, both in terms of content and the use of information and communication technology. The findings of the research also show that the support of mentors (from the Faculty of Social Work and field placements) is crucial for students to face the challenges in practice as it equips them with the knowledge of how to respond to challenges.
Keywords: kombinirana raziskava; mentoring; mentorstvo; mixed methodology; pandemic; pandemija; practical training; praktično usposabljanje; satisfaction; zadovoljstvo